(untitled) (Revista de Ciências Agroveterinárias, 2018)
This study aims to qualitatively and quantitatively characterize the semen of tambaqui (Colossoma macropomum) during the breeding season. Three samplings were made at regular intervals of approximately 30 days in the 2012/2013 breeding season. Ten adult males of at least three years old age were selected. To collect the semen, hormonal induction was performed with carp pituitary extract, and extraction occurred by abdominal massage. After collection, the semen was subjected to evaluation of motility, vigor, lifetime, ejaculate volume, and sperm concentration. Analysis of variance (ANOVA) and Tukey test were applied on quantitative variables, while the Freedman test was used with 0.05 significance on qualitative variables. No significant differences (p>0.05) were observed for most parameters evaluated. Sperm concentration significantly varied between samples (14.5, 3.7, and 8.3x109 sperm/mL) and lifetime decreased significantly between the second and third samples (267.8 e 98.5 seconds, respectively).